Taxes, Default Risk and Credit Spreads - WU, Chunchi (Institutional Knowledge at Singapore Management University, 2004)
Presents a general term structure model of defaultable bonds that assesses the potential effects of taxes. Effects of taxes on corporate bond spreads; Impact of tax omission on default rate estimation; Factor essential in evaluating firm performance and understanding whether investors are fully compensated for the risk they bear.